Left atrial strain reservoir in monitoring heart transplant paediatric patients. (8th February 2021) - Borrelli, N; Panebianco, M; Di Salvo, G; Alfieri, S; De Angelis, D; Chinali, M; Amodeo, A; Parisi, F; Guccione, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In heart transplant (HT) patients, high LV filling pressure is considered a marker of rejection and predictive of increased mortality. Purpose: Our study aims to correlate echocardiographic parameters to left-ventricular end diastolic pressure (LVEDP) at cardiac catheterization in transplant recipients. Methods: This was a retrospective study of 50 HT patients (54% male) who underwent heart transplantation in paediatric age (0-18 years-old). The echocardiographic evaluation was performed within three weeks from the left heart cardiac catheterization. From apical view, we measured: left atrial strain (LAS) indices [atrial contraction (εac), LA filling (reservoir phase, εres), and LA passive emptying (conduit phase, εcon)], mitral doppler E/A, E/e', global longitudinal strain (LVGLS) and strain rate. Results: Median LVEDP was 10 mmHg (IQR 8.25-12 mmHg) and had the best correlation with decreased εres (r= -0.56, p < 0.0001). The other LAS indices and mitral E/e' correlated less strongly with LVEDP (εac: r= -0.42, p = 0.004; εcon: r= -0.55, p= 0.0001; E/e': r = 0.28, p = 0.04). E/A, LVGLS and LVGLS rate did not correlate with LVEDP. By ROC analysis, εres ≤ 16.3% was predictive of elevated LVEDP with a good sensitivity (86%) and moderate specificity (57%). A multivariate analysis produced εres as the best predictor (p = 0.0001) for high LVEDP. Conclusions: Non-invasive εres seems to be a good surrogate of invasive LVEDP. Monitoring εres may be of value in HT patients to survey for rejection and graft disfunction.